The evolution of financial integration on selected European stock markets: A dynamic principal component approach - Elżbieta Majewska; Joanna Olbryś (Comparative Economic Research. Central and Eastern Europe, 2017)
The goal of this paper is to recognize the dynamics of financial integration across the European stock markets over the last two decades. We investigate two groups of markets: (1) three developed European markets in the U.K., France, and Germany; and (2) three emerging Central and Eastern European markets in Poland, the Czech Republic, and Hungary (CEE-3). The evolution of the integration process is analyzed using a dynamic principal component approach. The index of integration serves as a robust measure of integration. The empirical results reveal that the dynamics of integration across the whole group of markets increased significantly following the CEEC-3's accession to the European Union. An inverted U-shape in the index of integration has been found in this case. Moreover, the average index of integration was significantly different during the Global Financial Crisis compared to the pre-crisis period.
Keywords: C10; F36; F65; G01; G15; O52; O57; 330; european stock markets; dynamic principal component analysis; index of integration; Global Financial Crisis